Determinants of residential space heating expenditures in Great Britain - Helena Meier; Katrin Rehdanz (Kiel Institute for the World Economy (IfW), 2008)
In Great Britain several policy measures have been implemented in order to increase energy efficiency and to reduce carbon emissions. In the domestic sector, these targets can be achieved by improving space heating efficiency and, hence, decrease heating expenditures. However, before implementing policy measures it is necessary to better understand determinants of heating expenditures. In this paper, we examine determinants of heating expenditures which include socio-economic and building characteristics as well as heating technologies and meteorological observations. In contrast to most other studies, we use Panel data for investigating household's demand for heating in Great Britain. Our analysis covers 15 years, starting in 1991, and more than 5,000 households that have been re-interviewed annually; altogether our sample covers more than 64,000 households. Our empirical findings suggest that in Great Britain owners generally have higher heating expenditures than renters. These differences in expenditures can be explained by building characteristics. Renters mainly live in flats and most of the owners live in detached/semi-detached houses. Generally, flats are more energy efficient than houses. Our results also imply that a number of socio-economic criteria have a significant influence on heating expenditures, independent from the central heating fuel type. Policy measures should not only focus on insulation standards but also on different household types. Especially elderly people and households with children should be target groups.
Keywords: C23; D12; Q4; 330; Great Britain; space heating; income elasticity; price elasticity; Wärmeenergie; Heizungsanlage; Verbraucherausgaben; Elastizität; Wohnung; Wohneigentum; Energiesparen; Panel; Großbritannien